2000
DOI: 10.1128/jcm.38.11.4215-4218.2000
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Legionella pneumophila Using a Real-Time PCR Hybridization Assay

Abstract: A real-time PCR hybridization assay for Legionella pneumophila is described; the assay uses LightCycler (Idaho Technology) methodology to specifically detect 2.5 CFU/reaction, equivalent to 1,000 CFU/liter of starting water sample. The assay, including DNA extraction and confirmation of product identity, is completed within 90 min of receipt of a sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 14 publications
(12 reference statements)
0
30
1
1
Order By: Relevance
“…However, specific bacterial species are more frequently the focus for real-time PCR assays, especially when long culture times can be replaced by rapid and specific gene detection. Leptospira genospecies, Mycobacterium and Propionibacterium spp., Chlamydia spp., Legionella pneumophila and Listeria monocytogenes have all been detected and in some cases quantitated with the use of real-time PCR assays [41,[234][235][236][237][238][239][240][241][242][243][244][245][246].…”
Section: Bacteriamentioning
confidence: 99%
“…However, specific bacterial species are more frequently the focus for real-time PCR assays, especially when long culture times can be replaced by rapid and specific gene detection. Leptospira genospecies, Mycobacterium and Propionibacterium spp., Chlamydia spp., Legionella pneumophila and Listeria monocytogenes have all been detected and in some cases quantitated with the use of real-time PCR assays [41,[234][235][236][237][238][239][240][241][242][243][244][245][246].…”
Section: Bacteriamentioning
confidence: 99%
“…Several qPCR assays targeting Leg. pneumophila have been developed during the last few years (Ballard et al 2000;Wellinghausen et al 2001;Levi et al 2003;Joly et al 2006;Behets et al 2007). The use of qPCR in the direct enumeration of Leg.…”
Section: Introductionmentioning
confidence: 99%
“…The use of qPCR in the direct enumeration of Leg. pneumophila was evaluated in sample of natural water, hospital water and cooling tower water (Ballard et al 2000;Wellinghausen et al 2001;Levi et al 2003;Joly et al 2006). Moreover, some authors reported that the interpretation of qPCR could be influenced by the type of water samples (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On these occasions, a rapid detection of contamination is needed to minimize the risk of case appearance and ⁄ or to check the effectiveness of any corrective measures. Although the culture technique represents the gold standard, it takes up to 10 days before results are available and has a limited sensitivity, and inter-laboratory variations have been reported in diagnostic field, but not on water samples (Boulanger and Edelstein 1995;Ballard et al 2000;Tronel and Hartemann 2009). Thus, a more rapid, simple and reproducible technique for legionellae detection in environmental samples may be of special interest for routine laboratory applications.…”
mentioning
confidence: 99%